Design, Synthesis, and Neuroprotective Effects of a Series of Pyrazolines against 6-Hydroxydopamine-Induced Oxidative Stress - Özdemir, Ahmet; Sever, Belgin; Altıntop, Mehlika Dilek; Kaya Tilki, Elif; Dikmen, Miriş (Molecules (Basel, Switzerland), 2018)
Parkinson’s disease (PD) is a chronic, progressive, and age-related neurodegenerative disorder characterized by the loss of midbrain dopaminergic neurons caused by the accumulation of free radicals and oxidative stress. Based on the neuroprotective properties of 2-pyrazoline derivatives, in the current work, 1-(phenyl/4-substituted phenyl)-3-(2-furanyl/thienyl)-5-aryl-2-pyrazolines (3a–i, 4a–i) were synthesized via the cyclization of the chalcones (1, 2) with suitable phenylhydrazine hydrochloride derivatives. All these compounds were investigated for their neuroprotective effects using an in vitro 6-hydroxydopamine (6-OHDA)-induced neurotoxicity model of PD in the rat pheochromocytoma (PC-12) Adh cell line. In addition, some different pharmacokinetic parameters of all compounds were in silico predicted by the QikProp module of Schrödinger’s Maestro molecular modeling package. 4-Methylsulfonylphenyl substituted compounds 3h (20%) and 4h (23%) were determined as the most promising neuroprotective agents related to their inductive roles in cell viability when compared with the 6-OHDA-positive control group (43% and 42%, respectively). Moreover, in silico pharmacokinetic results indicated that all compounds were within the acceptable range intended for human use. According to both in vitro and in silico studies, compounds 3h and 4h draw attention as potential orally bioavailable therapeutic drug candidates against neurodegeneration in PD.